Rural Education from Native American Perspective - Jacques Seronde (Educational Considerations, 1986)
Rural educators speak often of the need to respect the rural culture - to not impose urban solutions on rural problems. Differences infinitely more immense appear when we examine education through the eyes of Native Americans.